2018
DOI: 10.1080/15592294.2018.1554521
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid exposure and altered DNA methylation in rat and human sperm

Abstract: Little is known about the reproductive effects of paternal cannabis exposure. We evaluated associations between cannabis or tetrahydrocannabinol (THC) exposure and altered DNA methylation in sperm from humans and rats, respectively. DNA methylation, measured by reduced representation bisulfite sequencing, differed in the sperm of human users from non-users by at least 10% at 3,979 CpG sites. Pathway analyses indicated Hippo Signaling and Pathways in Cancer as enriched with altered genes (Bonferroni p < 0.02). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
187
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(202 citation statements)
references
References 47 publications
10
187
0
5
Order By: Relevance
“…For instance, adult‐onset prediabetic conditions (Wei et al., ), obesity (Fullston et al., ), and cocaine‐seeking motivation (Le et al., ) all modify the DNA methylome in sperm. One recent study reported similar changes in DNA methylation in sperm between tetrahydrocannabinol (THC)‐treated rats and cannabis‐smoking adults (Murphy et al., ). Other studies have reported effects of cocaine and stress on histone modifications in developing or mature sperm at specific gene loci that coincided with altered expression of the same gene in adult offspring brain, suggesting cross‐generational epigenetic memory (Dias and Ressler, ; Vassoler et al., ).…”
Section: Effects Of Environmental Insults On Epigenetic Mechanisms Inmentioning
confidence: 85%
“…For instance, adult‐onset prediabetic conditions (Wei et al., ), obesity (Fullston et al., ), and cocaine‐seeking motivation (Le et al., ) all modify the DNA methylome in sperm. One recent study reported similar changes in DNA methylation in sperm between tetrahydrocannabinol (THC)‐treated rats and cannabis‐smoking adults (Murphy et al., ). Other studies have reported effects of cocaine and stress on histone modifications in developing or mature sperm at specific gene loci that coincided with altered expression of the same gene in adult offspring brain, suggesting cross‐generational epigenetic memory (Dias and Ressler, ; Vassoler et al., ).…”
Section: Effects Of Environmental Insults On Epigenetic Mechanisms Inmentioning
confidence: 85%
“…Using reduced representation bisulphite sequencing (RRBS) our group recently demonstrated that cannabis use in humans, and THC exposure in rats, is associated with decreased sperm concentrations and widespread changes in sperm DNA methylation [25]. Of the regions identified in humans, Discs-Large Associated Protein 2 (DLGAP2) exhibited significant hypomethylation in the sperm of cannabis-exposed men compared to controls (p < 0.05).…”
Section: Introductionmentioning
confidence: 99%
“…For disease significance, I first determined the overlap between genes showing differential methylation in sperm under various conditions and genes associated with certain diseases implicated earlier. The sperm samples included that of recreational users of cannabis 19 (Can), cigarette smokers 20 (Cig), enriched-risk cohort of fathers of autistic children 15 (Aut), men undergoing fertility treatment and showing association between differential sperm methylation and preconception urinary phthalate concentration 21 (Ph), exercise trained (ExT) and detrained (ExD) individuals 22 , men with experience of childhood abuse 23 (ChA), veterans with posttraumatic stress disorder 24 (PTSD), and obese men before (Ob) and after one week (Obw) or one year (Oby) of bariatric surgery 25 . The corresponding studies were identified through manual search for relevant literature.…”
Section: Resultsmentioning
confidence: 99%